2004
DOI: 10.1007/bf03033741
|View full text |Cite
|
Sign up to set email alerts
|

Human osteosarcoma xenografts and their sensitivity to chemotherapy

Abstract: Despite the increased survival rates of osteosarcoma patients attributed to adjuvant chemotherapy, at least one third of the patients still die due to their disease. Further improvements in the management of osteosarcoma may rely on a more individualised treatment strategy, as well as on the introduction of new drugs. To aid in the preclinical evaluation of new candidate substances against osteosarcoma, we have established 11 human osteosarcoma xenograft lines and characterised them with regard to response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 30 publications
1
28
1
Order By: Relevance
“…Aloj et al [53] found a significant correlation between the absence of 99m Tc-sestamibi uptake and overexpression of Bcl-2 in breast cancer cell lines. Multidrug resistance-associated protein 1 (MRP1) can also be overexpressed in tumour cells, conferring drug resistance [23,54]. Decreased uptake or enhanced efflux of 99m Tc-sestamibi can be mediated by MRP1 [19,23].…”
Section: Discussionmentioning
confidence: 99%
“…Aloj et al [53] found a significant correlation between the absence of 99m Tc-sestamibi uptake and overexpression of Bcl-2 in breast cancer cell lines. Multidrug resistance-associated protein 1 (MRP1) can also be overexpressed in tumour cells, conferring drug resistance [23,54]. Decreased uptake or enhanced efflux of 99m Tc-sestamibi can be mediated by MRP1 [19,23].…”
Section: Discussionmentioning
confidence: 99%
“…The animals were maintained, and experiments and assessment of chemotherapy response were conducted as described previously (12). In brief, the animals were 4 to 6 weeks old at the day of tumor implantation.…”
Section: Methodsmentioning
confidence: 99%
“…Ten human osteosarcoma xenografts were used, eight of which have been described previously (12), and in addition, two newly established xenografts were included. These originated from a 32-year-old male with an extremity located fibroblastic osteosarcoma of malignancy grade 4 (GKAMX) and from a 13-year-old female with an extremity located osteoblastic osteosarcoma of malignancy grade 4 (CTPX).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study of GSTP1 expression in samples from pediatric patients with osteosarcoma showed that GSTP1 expression might have a bearing on the outcome of treatment with chemotherapy (14). Another study by Bruheim et al (15) showed that the GSTP1 mRNA level was inversely correlated with doxorubicin growth inhibition in human osteosarcoma xenografts.…”
Section: Introductionmentioning
confidence: 99%